Anï¿½lisis de la morfometrï¿½a y de la dimensiï¿½n fractal en la lesiï¿½n del tejido muscular esquelï¿½tico expuesto en la combinaciï¿½n de los tratamientos de crioterapia y ultrasonido - Koike, Tatiana Emy [UNESP]; Camargo, Regina Celi Trindade [UNESP]; Ozaki, Guilherme Akio Tamura; Castoldi, Robson Chacon; Seraphim, Patrï¿½cia Monteiro [UNESP]; Oikawa, Sï¿½rgio Minoro [UNESP]; Camargo Filho, Josï¿½ Carlos Silva [UNESP] (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2016)
The aim of this study was to analyze the effects of an association of cryotherapy and therapeutic ultrasound on the treatment of muscle injured by impact. Fifty-five Wistar rats were divided into five groups (n = 11), Acute Injury (AI), Injury (I), Cryotherapy (CR), Therapeutic Ultrasound (TU) and Association of Cryotherapy and Therapeutic Ultrasound (CRTU). The CR and CRTU groups received applications of Cryotherapy three times (immediately, 24 and 48 h after injury) of 20 minutes duration. The TU and CRTU groups received applications of Therapeutic Ultrasound for seven days, for five minutes, in pulsed mode, 0.5 w/cm intensity, frequency 1 MHz. Body mass and gastrocnemius mass were analyzed. In addition to histological slides stained with hematoxylin and eosin used for morphometric analysis, picrosirius dye was used for quantification of collagen by Fractal Dimension (FD). The results of the intra-group analysis showed lower body mass and gastrocnemius in the CRTU group in relation to the AI (p = 0.001), I (p = 0.001), CR (p = 0.001) and TU groups (p = 0.001), and lower values of FD to quantify collagen in the CRTU group in relation to the AI (p = 0.007) and CR groups (p = 0.014). In summary, the present study showed that the association of Cryotherapy with Therapeutic Ultrasound promoted better results in the aspects analyzed compared to application of the therapies in isolation.
Morphometric and fractal analysis of injured skeletal muscle tissue subjected to a combination of treatments; cryotherapy and therapeutic ultrasound
Keywords: Collagen; Cryotherapy; Fractal; Regeneration; Ultrasound therapy